Accuracy of Global Navigation Satellite System (GNSS) Positioning Under Tree Canopy: Evaluating the Effect of Extended Antenna Height and Multiple GNSS Systems - Pirti, Atinc; Ucar, Zennure; Kurtulgu, Zumrut; Eren, Mehmet (SPRINGER, 2025)
Accurate and precise information is vital in forestry and urban environments. Global Navigation Satellite System has become popular for navigating and recording positions, monitoring and mapping purposes. However, the integration of GNSS has been slower in forestry and urban environments because signals are subject to attenuation and blocking in environments covered by tree canopies and urban canyons, which affects positioning accuracy by causing a multipath effect. Still, this technology is steadily replacing traditional navigation and mapping techniques. In this study, the main objective is to investigate the use of the extended antenna height of the GNSS receiver during the measurements in order to reduce the multipath effects in an urban environment. Also, we evaluated the accuracy of two different multi-GNSS satellite configurations by comparing them with the measurements from the total station (reference). Based on the results, using the extended antenna height (6 m) above the tree canopy along with multi-GNSS (two satellite configurations) offered higher accuracy with positional error of 1 cm for horizontal and 2 cm for vertical accuracy. Additionally, when compared to two different multi-GNSS satellite configurations, multi-GNSS with four satellite configurations had higher accuracy than multi-GNSS with two satellite configurations under the tree canopy cover. Our findings indicated that the extended antenna and multi-GNSS systems reduced the multipath effect due to canopy cover blocking and improved the accuracy and precision in urban environments. These results contribute to the ongoing evaluation of recent GNSS technologies.
Keywords: Multi-GNSS; Accuracy; Precision forestry; Urban tree cover; GPS; IGS; Environmental Sciences & Ecology; Remote Sensing